COMBINA: The EAAD four-level approach for depression and suicide prevention and wellbeing promotion in the community and vulnerable populations. A cross-country study protocol from the MENTBEST project - Bridget Hogg; Evelien Coppens; Daniela L. Gatto; Cristina de Córdoba-Gil; José Luis Ayuso Mateos; Keti Bakiu; Aileen Callanan; Arlinda Cerga Pashoja; Virgínia Conceição; Evgenia Dandi; Maria Faurholt-Jepsen; Christina Katsoridou; et al. (PLoS ONE, 2026)
Depression and suicide are leading public health problems requiring complex multilevel interventions. This study protocol details the COMBINA trial, which expands the evidence-based European Alliance Against Depression (EAAD) Community-Based 4-level intervention to also focus on improving wellbeing and tailored to five groups with increased vulnerability to depression: young people, older people, migrants/refugees, the long-term unemployed, and people with an existing mental health condition. In this prospective, non-randomised controlled trial, the COMBINA project will be newly implemented during a 24-month period, from late 2024 to late 2026, in five regions in Albania, Estonia, Greece, Ireland, and Spain. These regions will be compared to five control regions in the same countries, chosen to reflect a similar context, size, and sociodemographic characteristics. Main outcomes are a comparison between the intervention and control regions in the rates of deaths by suicide and hospitalisations for suicide attempts and the levels of wellbeing, depressive symptoms, anxiety symptoms, depression-related stigma, and willingness to seek psychological help in the general population. A process evaluation and economic evaluation will also be conducted. This intervention protocol also details the steps taken to promote successful implementation across a range of different cultural and regional contexts, with challenges including different existing mental health resources and differing capacities for the population to use digital tools. The COMBINA project includes co-creation, whereby materials and implementation strategy were designed with people from the vulnerable groups. The trial is funded by the European Union (grant agreement no. 101080651 and carried out according to the Declaration of Helsinki. Ethical approval has been obtained in all participating countries. The results will be published in peer-reviewed academic journals, presented at scientific meetings and disseminated through COMBINA stakeholders, with participation from the co-creators. This trial protocol (version 1.1, 24/10/2024) was registered in the ISRCTN registry (ISRCTN10521127) on 14/11/2025 ( https://www.isrctn.com/ISRCTN10521127 ).